2013
DOI: 10.1007/s10926-013-9436-y
|View full text |Cite
|
Sign up to set email alerts
|

What Work Means to People with Work Disability: A Scoping Review

Abstract: The exploration of the meaning of work has been shown to provide important understanding of the experience of work and disability. This understanding can guide rehabilitation professionals in their interventions with the work disabled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
107
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(118 citation statements)
references
References 56 publications
7
107
0
4
Order By: Relevance
“…The potential for a lack of fit between a person and a job is obvious in any review of TBI symptoms, which include cognitive difficulties (e.g., memory, reading, listening, organizing, and reasoning difficulties), emotional issues (e.g., problems with depression, anger management, and anxiety), physical effects (e.g., headaches, speech problems, lack of coordination, and fatigue), and psychosocial problems (e.g., feeling misunderstood, being bullied or teased, and being perceived by others as malingering or not performing consistent with capabilities [2,5,7]. Most people with TBI are employed at the time of their injuries, but only 31 percent are employed one year later [8].…”
Section: Tbi's Impact On Personal Functioning and Job Retentionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential for a lack of fit between a person and a job is obvious in any review of TBI symptoms, which include cognitive difficulties (e.g., memory, reading, listening, organizing, and reasoning difficulties), emotional issues (e.g., problems with depression, anger management, and anxiety), physical effects (e.g., headaches, speech problems, lack of coordination, and fatigue), and psychosocial problems (e.g., feeling misunderstood, being bullied or teased, and being perceived by others as malingering or not performing consistent with capabilities [2,5,7]. Most people with TBI are employed at the time of their injuries, but only 31 percent are employed one year later [8].…”
Section: Tbi's Impact On Personal Functioning and Job Retentionmentioning
confidence: 99%
“…DillahuntAspillaga et al [14] reported the results of a needs assessment in Florida in which participants with TBI identified employment as their number one priority. As reiterated in multiple sources, returning to work provides people with access to income, self-esteem, identity, and social status [7,14,15], yet traditional vocational rehabilitation services have only partially succeeded in helping people with TBI return to work. As Dillahunt-Aspillaga et al stressed, a need exists for vocational rehabilitation interventions that directly address the problems that individuals with TBI encounter in employment.…”
Section: Tbi's Impact On Personal Functioning and Job Retentionmentioning
confidence: 99%
“…Work as an occupation of daily living holds benefits for any person participating in it 1,2,3,4 . It has been established though, that people with psychiatric and intellectual disabilities experience extensive barriers to participation in work as employment (distinguished here from unpaid work), inclusive of stigma and complex support needs 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Patient's desire to return to work (RTW) after a disabling illness or injury has been shown to be a consistent theme across conditions [1]. Thus it is not surprising that empirical studies identified work reintegration as one the most important and challenging goals in the rehabilitation journey of burn survivors [2].…”
Section: Introductionmentioning
confidence: 99%